Pengaruh Brand Image, Mutu Produk dan Persepsi Harga terhadap Keputusan Pembelian Merchandise Miniso Ambarrukmo Plaza Mall Yogyakarta - Regita Ratna Hediyati; Yunita Fitri Wahyuningtyas (Universitas Nusantara PGRI Kediri, 2024)
Miniso presents a variety of middle class products at economical selling prices so that they are very popular with many people, especially millennials. The aim of this research is to evaluate the variables listed in the observations. Researchers analyze using quantitative methods. The information collection strategy is in the form of a general description and survey with a questionnaire as a paraga. The sample in this research consisted of 100 purchasing clients at Miniso Ambarrukmo Plaza Mall Yogyakarta, using a purposive sampling testing strategy and the IBM SPSS 25th edition statistical program. As shown by the research results, brand image, product quality and price perceptions influence purchasing choices.